Socioeconomic and demographic characteristics and health condition of elderly people from a family health program in Porto Alegre, Brazil (Revista Latino-Americana de Enfermagem, 2006)
This epidemiological and exploratory-descriptive study aimed to identify the socioeconomic and demographic features, as well as the health and disease condition of elderly people from a Family Health Program in Porto Alegre, Brazil, with the purpose of contributing to the planning of health actions for this population. Data from 98 elderly people were collected through a home survey by means of a semistructured instrument. The mean age of the interviewed subjects was 69.5. Sixty-one participants (62.2%) were women; 40 (40.8%) were married and 77 (78.6%) did not have remunerated work. Most men (64.9%) had a companion, against 26.2% of women with a partner. As to health, 80.6% reported suffering from some pathology, especially diseases of the circulatory system, reported by 55.1% of the interviewees. Although the collected data are in line with other studies, knowledge about them is important to adapt health actions by the Family Health Program team under study, in order to offer better care to these elderly people.